Vatikan II setelah 50 Tahun: Quo Vadimus - Heatubun, Fabianus Sebastian (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Pope Francis’s statement “I am the Vatican II” sounds a manifesto. To which direction is the wind blowing the Church’s ark, we might have already guessed. The existing dichotomy between the liberal and the conservative as well as the tension between the primacies of the pastoral and the dogmatic will yet be conflicting and colliding with each other. After 50 years, the 2nd Vatican Council and the ongoing future discussions about the basic pastoral directions within the Catholicism are to this day white-hot. The Pope could be anyone. But theologians, for these are who make the lineamenta of a new document, will continue to colour the trend of the Church in giving responses to the signs of the time. The future of Catholicism will not be viewed as limited as the lens of the Vatican II. The future humanism will challenge the Church with wider and more complex considerations rather than dwelling on the problems of dialogue with other religions apologetically or racketing with traditionalism, liberalism, and sekularism. There are pressing matters such as ecology, global warming, terrorism, and the sprawling gap between the poor and the rich. Macro-ethics has become more imperative than micro-ethics. The Catholic Church is called out to create “a better world for all” – the Kingdom of God that is inclusive and at a stroke pluralistic.